(NmEHANI^ESKIE SWOJSTWA I SOKRATITELXNAQ SPOSOBNOSTX UTOMLENNYH MY[C ^ELOWEKA (B/s - (NmANUKQN(B, (NtAKWOR wAGANOWI^s; (NfELXDMAN(B, (Na(B.(Ng(B.s ((NeREWAN (B:s (NaJASTAN(B,s, 1984)
(NrEZ@ME(B: (NANGL(B. (NQZ(B.s
(NbIBLIOGR(B.: (NS(B. 145-176s
Keywords: (NfIZIOLOGIQs